A Novel Technological Review on Fast Charging Infrastructure for Electrical Vehicles: Challenges, Solutions, and Future Research Directions - Ravindran, Mohammed Abdullah; Nallathambi, Kalaiarasi; Vishnuram, Pradeep; Rathore, Rajkumar Singh; Bajaj, Mohit; Rida, Imad; Alkhayyat, Ahmed (Alexandria engineering journal, 2023)
Nowadays, the use of electric vehicles (EVs) is increasing as the charging infrastructure for these EVs is necessary. The highly rapid loading technology can charge cars and looks like refilling fuel in vehicles. This article covers the review of sophisticated loading infrastructure, several topologies of converters, and quick-charging technologies to meet future requirements. Specifically designed for AC/DC front-end stage and non-isolated and isolated DC/DC converters are suitable for Fast Charging Stations (FCS) and their applications that meet automotive battery isolation requirements. In addition, evaluate the benefits of converting the medium voltage to low voltage at the FCS by substituting a Solid-State Transformer (SST). Also, this paper presents a topological survey of available charging stations. The performance of various topologies of charging stations is discussed based on grid support, modularity, power density, and other factors.